Analisis Keselamatan dan Kesehatan Kerja (K3) Pembangunan Reservoir dengan Metode Hazard and Operability (HAZOP) - Jubiana, Ega Pratiwi; Rosdiana, Rosdiana; Pratiwi, Yunita Eka (Universitas Muhammadiyah Kendari, 2025)
This study analyzes potential hazards and risk levels in the reservoir construction project in Pela Village using the Hazard and Operability Study (HAZOP) method. Data were collected through observations, interviews, and questionnaires. The results show several moderate to high risks, including falls from heights, struck-by hazards, excavation collapse, dust exposure, and heavy equipment accidents. These risks are mainly caused by worker negligence, inconsistent PPE use, and inadequate supervision. Recommended controls include mandatory PPE, safety training, warning signs, and safe work procedures. The HAZOP method proved effective in identifying hazards and improving OSH practices.